Determinacion de las perdidas de cosecha en el cultivo el tomate (Lycopersicon esculentum, Mill.) - Liriano Gonzalez, R.=700 1 Sanchez Llanes, P.; Fabelo Peguero, M.; Cruz Alvarez, R.; Verano Huerta, B.
(Es, En)
Ilus., 5 ref.
Keywords: LYCOPERSICON ESCULENTUM; COSECHA; PERDIDAS; CUBA